2018
DOI: 10.1016/j.cpc.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

CoFFEE: Corrections For Formation Energy and Eigenvalues for charged defect simulations

Abstract: Charged point defects in materials are widely studied using Density Functional Theory (DFT) packages with periodic boundary conditions. The formation energy and defect level computed from these simulations need to be corrected to remove the contributions from the spurious long-range interaction between the defect and its periodic images. To this effect, the CoFFEE code implements the Freysoldt-Neugebauer-Van de Walle (FNV) correction scheme. The corrections can be applied to charged defects in a complete range… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 56 publications
2
40
0
Order By: Relevance
“…This issue was first pointed out by Noh et al [1] (and later on reported at least in Refs. [2,3]), who suggested using a fifth-order polynomial for the fitting.…”
mentioning
confidence: 99%
“…This issue was first pointed out by Noh et al [1] (and later on reported at least in Refs. [2,3]), who suggested using a fifth-order polynomial for the fitting.…”
mentioning
confidence: 99%
“…The formation energy of charged sulfur vacancies computed at the DFT level need to be correctedfor the spurious electrostatic interaction between the charge and its periodic images. The electrostatic corrections are computed using the CoFFEE code [64].…”
mentioning
confidence: 99%
“…Note that this expression neglects higher order terms, which may not be negligible for thicker slabs. 16,41,42 However, the error here for monolayer MoS 2 (0.31 nm thickness) should be substantially less than 0.1 eV according to our previous studies, for example, the error for monolayer black phosphorus (0.21 nm thickness) is 0.04 eV and the error for thicker bilayer black phosphorus (0.77 nm thickness) is 0.13 eV. 19 Here IE ∞ is obtained at a fixed L Z = 40 Å with L x × L y ranging from 5 × 5 to 7 × 7.…”
Section: Calculation Of Ionization Energies Ie ∞mentioning
confidence: 99%